DONATION AND TRANSPLANTATION OF ORGANS AND TISSUES IN A BIOETHIC DIMENSION: A SYSTEMATIC REVIEW - Andrade, Ana Maria Lima Carneiro de; Modesto, Caroline Pereira; Albuquerque, Lucas Tavares Cruz de; Granja, Taelis Araujo; Albuquerque, Ana Beatriz Tavares Cruz de; Silva, Cláudio Gleidiston Lima da; Malheiro, Djailson Ricardo (Amadeus International Multidisciplinary Journal, 2020)
Abstract: Organs and tissue transplantation between humans is a relatively current tool in medical practice and is based on the implantation of a solid organ or tissue from a living donor or corpse to a receiver. From the transplantation practice on an ascending scale practiced all over the world, linked to the growing demand for the health system, emerged the need to implement normative ethical concepts to regulate these procedures. Methodology: It is a systematic review whose data were extracted from the PubMed and VHL databases. In the first one, the descriptors “bioethics” and “organ transplantation” were used using the logical operator AND that resulted in 731 articles and, after refinement, the sample registered 02 (two) articles. In the second cited base, the search was performed with the same descriptors (n = 536), but only 07 were selected. Results: We emphasize the transplantation concept and its attributions, besides exploring legislative changes in Brazil and in the world, ethical and bioethical debates on the subject and the medical-legal panel involved. Conclusion: Faced with the death expectation, organ transplantation emerges as a safe method with the potential to increase longevity and quality of the patient life, nevertheless, ethical dilemmas arise in this process. Keywords: Bioethics. Tissues and organs obtainment. Organ transplantation.